THE EFFECT OF PRODUCT QUALITY, PRICE, AND LOCATIONON THE PURCHASE DECISION OF GAYO COFFEE POWDER AT RAKAN COFFEE STORE IN ACEH TENGAH REGENCY - Laila Tussaa’dah; Halida Bahri; Mohd. Heikal; Jullimursyida (RADJA PUBLIKA, 2025)
This study aims to determine the partial effect of the variables Product Quality, Price, and Location on Purchase Decision. The data used in this study are primary data obtained by distributing questionnaires to 100 respondents. The questionnaire was tested using validity and reliability tests, with reliability measured using Cronbach’s Alpha method. Classical assumption tests include the normality test, multicollinearity test, and heteroscedasticity test. Hypothesis testing was conducted using the t-test (partial) and the coefficient of determination (R²). The data analysis technique employed was multiple linear regression with the help of SPSS version 26.